Green investment in the EU and the US: Markup insights - Anastasia Bruni (Fondazione Eni Enrico Mattei (FEEM), 2025)
This paper examines the effect of green investments on market power. I measure the market power as markup following the method provided in De Loecker and Warzynski (2012). For green investments, I consider specifically the investments of firms in energy efficient technologies, both as the binary variable and as the continuous variable. This allows the examination of how the presence of such investments as well as their intensity affect markups. I use firm, age, year, sector and country fixed effects with a representative sample of indicatively 12,000 firms from the European Investment Bank Investment Survey (EIBIS) in the panel from 2016 to 2022. I find the positive and statistically significant relationship that holds also when applying the 2SLS-IV methodology. This study is particularly relevant for firms that are willing to increase their market power and to improve their environmentally friendly image in the eyes of their customers without the need of engaging in greenwashing practices. Instead, the firms are invited to consider energy efficiency investments as a concrete way of improving both their markups and the loyalty of their customers.
Keywords: Q56; L11; D22; C36; O13; 330; green investment; markup; market power; instrumental variable